2018
DOI: 10.1128/jvi.00413-18
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of the Murine Norovirus Protruding Domain and Soluble CD300lf Receptor Complex

Abstract: Human noroviruses are the leading cause of acute gastroenteritis in humans. Noroviruses also infect animals, such as cows, mice, cats, and dogs. How noroviruses bind and enter host cells is still incompletely understood. Recently, the type I transmembrane protein CD300lf was identified as the murine norovirus receptor, yet it is unclear how the virus capsid and receptor interact at the molecular level. In this study, we determined the X-ray crystal structure of the soluble CD300lf (sCD300lf) and the murine nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 42 publications
(60 reference statements)
1
41
0
Order By: Relevance
“…Recently reported co-crystal structures of murine norovirus P-domains in complex with their protein receptor, CD300lf, revealed the receptors bind at the interfaces between three P-domain spikes when superimposed on the map of the assembled virus (19)(20)(21). In GII.4 T=4 particles, the interface between dimeric Pdomain spikes forms around the 20 icosahedral three-fold axes between Dsubunits, and the 60 quasi three-fold axes between A, B and C subunits (Fig.…”
Section: Protruding Spike Domainmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently reported co-crystal structures of murine norovirus P-domains in complex with their protein receptor, CD300lf, revealed the receptors bind at the interfaces between three P-domain spikes when superimposed on the map of the assembled virus (19)(20)(21). In GII.4 T=4 particles, the interface between dimeric Pdomain spikes forms around the 20 icosahedral three-fold axes between Dsubunits, and the 60 quasi three-fold axes between A, B and C subunits (Fig.…”
Section: Protruding Spike Domainmentioning
confidence: 97%
“…The addition of either EDTA or 1,10-phenanthroline that preferentially chelates Zn 2+ caused an over three-fold decrease in the number of intact VLPs observed and the metal density disappeared in the asymmetric and symmetric reconstructions from the remaining intact particles, whereas EGTA, which preferentially chelates Ca 2+ , did not cause such changes. The infectivity of murine norovirus and feline caliciviruses that do not bind HBGAs have been reported to be metal-dependent (19,20,22). Moreover, GII.2 VLPs were reported to bind HBGAs when mixed with GII.2-positive patient stool, underscoring the involvement of co-ligands (23).…”
Section: Asymmetric Reconstruction Of Zn 2+ Binding That Affects Shelmentioning
confidence: 99%
“…P2 is the target for several neutralizing monoclonal antibodies for both HNoV and MNoV and contains the receptor binding site for MNoV [12,13]. Co-crystal structures and mutagenesis studies have identified that the CC' and CDR3 loops of CD300lf directly bind to a cleft between the AB' and DE' loops of the MNoV VP1 P2 subdomain [13,15,19]. Each CD300lf binds one P2 monomer, albeit at relatively low affinity, suggesting that norovirus-receptor interactions are largely driven by avidity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies have shown that caliciviruses have a common overall organization of T=3 icosahedral symmetry and are comprised of 180 copies of VP1 (7, 8, 23-25). Within the asymmetric unit, VP1 adopts three quasi-equivalent conformations, termed A, B, and C (8).…”
Section: Introductionmentioning
confidence: 99%